Macrozoobenthos Community at the Pond Culture Area in Malakosa Coastal, Parigi-Moutong, Central of Sulawesi - PETRUS RANI PONG-MASAK; ANDI MARSAMBUANA PIRZAN (Biodiversitas Journal of Biological Diversity, 2006)
The research have been conducted in the coastal area of Malakosa Parigi Moutong, Central of Sulawesi. The aimed of this research were to study the differences of community structure of macrozoobenthos and relationship among substrate (organic matter, sand, clay, silt, SO4 and Fe contents) with species number and biodiversity indices. Stratified random sampling in the soil conducted through grabbed the soil in the plots each size of 25x25x10 cm3 representatives station which including; the beach, mangrove, new pond close to the mangrove, the traditional pond, semiintensive pond with three replication respectively. Macrozoobenthos was preseved in 10% formalin solution and it identfication than counting of individual and species numbers, diversity, evenness and dominance indices. Water and soil qualities analyzes each station. Results showed that macrozoobenthos community in mangrove and the beach were better than the breakishwater pond which were pointed by diversity indices and species number. Macrozoobenthos community was under the influence of organic matter and SO4 contens in the soil, were increasing of organic matter and SO4 followed by decreasing of macrozoobenthos community in contrast with Fe content increase so macrozoobenthos community increase. Water and soil qualities in Malakosa coastal waters to support water organism life so that it areal suitable developed for aquaculture.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: macrozoobenthos, structure, substrate, Coastal of Malakosa